Relationship between performance culture, organisational structure and organisational innovativeness among administrators in higher education institutions - Hafit, Nor Intan Adha (2017)
The empirical evidence indicates that in order to survive and achieve long-term viability, a higher education institution must show an impressive performance. In facing the challenges from the global education market, strategic planning must be in place for the Higher Education Institutions (HEI) to capitalise on transformations for excellence. In line with the aspiration of Malaysia to be a competitive educational centre of excellence and international education centre in Southeast Asia, HEI in Malaysia are expected to achieve academic excellence through innovation. Therefore, it is important to review the innovations of HEI organisations. Meanwhile, organisational learning is the key to enhancing organisational reforms. Hence, this study reviews the correlations between the performance culture, organisational structure, organisational learning, and organisational innovativeness through the lens of a dynamic capability theory, knowledge-based view, and a structural contingency theory. This study used a descriptive and correlation study design with a comprehensive sample. A total of 273 administrators from six HEIs, namely Universiti Utara Malaysia (UUM), Universiti Teknologi MARA (UiTM), Universiti Malaysia Kelantan (UMK), Universiti Sains Islam Malaysia (USIM), Universiti Malaysia Sarawak (UNIMAS), and Universiti Tun Hussein Onn Malaysia (UTHM), representing a number of areas in Malaysia were randomly selected. Seven hypotheses were examined to identify whether or not each variable is associated with an organisational innovativeness. A descriptive analysis and Amos structural equation modelling version 23.0 were adopted to examine the adequacy of the hypothesis model as well as the correlation between the variables. By using the path analysis, this study gained support for seven hypotheses. In the Malaysian HEI environment, the performance culture is correlated with organisational learning (H1), organisational structure is correlated with organisational learning (H2), organisational learning is correlated with organisational innovativeness (H3), performance culture is correlated with organisational innovativeness (H4), organisational structure is correlated with organisational innovativeness (H5), performance culture is correlated with organisational innovativeness which are mediated by organisational learning (H6), and finally, organisational structure is correlated with organisational innovativeness which are mediated by organisational learning (H7). This study also exposes that all hypotheses provide positive support. This indicates that organisational learning is important in ensuring that organisational innovativeness can be enhanced to be more innovative and productive, facilitated by the performance culture and organisational structure. This study contributes uniquely towards the research by forming future frameworks, empirically combining the basic findings with theoretical descriptions from the information. The study also highlights a number of implications and recommendations for policies and practices towards organisational reformation enhancements in HEI. In the HEI context, this field of research is fairly new and as such it is important to reduce the gap between the limited empirical works for this topic, especially in Malaysia. From the perspective of theorists, this study opens up a new vision pertaining to organisational learning as a predictor of organisational innovativeness.